If it's not what You are looking for type in the equation solver your own equation and let us solve it.
10q-9q+3=11
We move all terms to the left:
10q-9q+3-(11)=0
We add all the numbers together, and all the variables
q-8=0
We move all terms containing q to the left, all other terms to the right
q=8
| 2(1+7x)=282 | | -28x-26+8x+12=-304 | | 0=5y^2-10y | | −4x+6=−2x–4 | | 25c=325 | | (4y-10)=-2 | | 8x-31=-159 | | 3x-12=5+7x/6 | | 5(6x+9)=375 | | -14=-2(m+14) | | 9+4c=–7+2c | | 8x+0.4=8.4 | | n-31=2 | | 6(1+2x)=234 | | 6(r-11)=15-4r | | 9p-12=10p | | 6=246a | | 1.2x=6.3 | | 7m−4−9m−36=0 | | (3x-24)=0 | | 1/3y+2=12 | | 2y+2+15y+3=3y-3 | | x=102 | | -5(2x+3)=-45 | | 156=6(2+x) | | –14=–2(m+14) | | 31=-3d+7 | | (y2−6y+2)−(3y2+7y−1)= | | 4x+7+5x+11=90 | | -3(y-15)=-6 | | y=12-41 | | 2-5x=-3(x+1)-2x+5 |